2020
DOI: 10.1182/blood.2019004326
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bcl-2 members after ibrutinib or venetoclax uncover functional hierarchy in determining resistance to venetoclax in CLL

Abstract: Chronic lymphocytic leukemia (CLL) cells cycle between lymph node (LN) and peripheral blood (PB) and display major shifts in Bcl-2 family members between those compartments. Specifically, Bcl-XL and Mcl-1, which are not targeted by the Bcl-2 inhibitor venetoclax, are increased in the LN. Since ibrutinib forces CLL cells out of the LN, we hypothesized that ibrutinib may thereby affect expression of Bcl-XL and Mcl-1 and sensitize CLL cells to venetoclax. We investigated expression of Bcl-2 family members in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
95
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 43 publications
14
95
1
2
Order By: Relevance
“…As the sensitivity to BH3 mimetics depends largely on the ratio of the expression of proapoptotic and antiapoptotic proteins, it was hypothesized early on that an increase in anti-apoptotic proteins following venetoclax exposure would confer resistance to Bcl-2 inhibition [ 71 , 72 ]. Various studies have demonstrated that venetoclax-associated overexpression of Mcl-1 and Bcl-X L can confer resistance to the drug in vitro and in vivo [ 23 , 24 , 72 , 73 , 74 , 75 , 76 ]. Recently it has been postulated that among the Bcl-2 family members, Bcl-X L is more relevant for the development of venetoclax resistance, as functional analyses have shown that proapoptotic proteins preferably interact with Bcl-X L when both anti-apoptotic proteins are present [ 24 ].…”
Section: Mechanisms Of Venetoclax Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…As the sensitivity to BH3 mimetics depends largely on the ratio of the expression of proapoptotic and antiapoptotic proteins, it was hypothesized early on that an increase in anti-apoptotic proteins following venetoclax exposure would confer resistance to Bcl-2 inhibition [ 71 , 72 ]. Various studies have demonstrated that venetoclax-associated overexpression of Mcl-1 and Bcl-X L can confer resistance to the drug in vitro and in vivo [ 23 , 24 , 72 , 73 , 74 , 75 , 76 ]. Recently it has been postulated that among the Bcl-2 family members, Bcl-X L is more relevant for the development of venetoclax resistance, as functional analyses have shown that proapoptotic proteins preferably interact with Bcl-X L when both anti-apoptotic proteins are present [ 24 ].…”
Section: Mechanisms Of Venetoclax Resistancementioning
confidence: 99%
“…Various studies have demonstrated that venetoclax-associated overexpression of Mcl-1 and Bcl-X L can confer resistance to the drug in vitro and in vivo [ 23 , 24 , 72 , 73 , 74 , 75 , 76 ]. Recently it has been postulated that among the Bcl-2 family members, Bcl-X L is more relevant for the development of venetoclax resistance, as functional analyses have shown that proapoptotic proteins preferably interact with Bcl-X L when both anti-apoptotic proteins are present [ 24 ]. Guièze and colleagues have performed an extensive analysis including genome-scale screens in a Bcl-2-driven lymphoma cell line and integrated expression profiling and identified Mcl-1 overexpression and BIM sequestration as a resistance-conferring mechanism to venetoclax treatment [ 23 ].…”
Section: Mechanisms Of Venetoclax Resistancementioning
confidence: 99%
See 3 more Smart Citations